Erratum: Sun, X.; et al. Folic Acid and PEI Modified Mesoporous Silica for Targeted Delivery of Curcumin. Pharmaceutics, 2019, 11, 430 - Xiaoxiao Sun; Nan Wang; Li-Ye Yang; Xiao-Kun Ouyang; Fangfang Huang (MDPI AG, 2020)
The authors wish to make the following corrections to this paper [1]: [...]